2013
DOI: 10.1021/jf304553g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Baicalein in Hct116 Cells and Caenorhabditis elegans: Activation of the Nrf2 Signaling Pathway and Prolongation of Lifespan

Abstract: Baicalein is a major compound of extracts derived from Scutellaria baicalensis Lamiaceae, which are used as food supplements. Baicalein possesses a high radical scavenging activity and decreases intracellular reactive oxygen species in Hct116 human colon carcinoma cells and in Caenorhabditis elegans . It activates Nrf2, a key transcription factor that binds to the antioxidant responsive element (ARE): Baicalein causes a nuclear accumulation of Nrf2, increases ARE-dependent luciferase activity, and enhances the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…Other compounds derived from the Chinese herb, such as wogonin [24], luteolin [25] and negletein [26], can have a synergistic effect on prevention and suppression of CRC as well. Signaling pathways are involved in its function of anti-CRC, including activation of the Nrf2 signaling pathway [27] and attenuation of the MAPKs and PI3K-Akt activation [28]. As for other common malignant tumors, several reports have revealed various kinds of signal paths mediated by baicalein [8,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds derived from the Chinese herb, such as wogonin [24], luteolin [25] and negletein [26], can have a synergistic effect on prevention and suppression of CRC as well. Signaling pathways are involved in its function of anti-CRC, including activation of the Nrf2 signaling pathway [27] and attenuation of the MAPKs and PI3K-Akt activation [28]. As for other common malignant tumors, several reports have revealed various kinds of signal paths mediated by baicalein [8,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that baicalein activates Nrf2, a key transcription factor that regulates inflammation, and enhances the expression of HO-1 in Hct116 human colon carcinoma cells (Havermann et al, 2013). To examine the effect of BG on Nrf2 activation, we took RAW 264.7-derived reporter cells that harbors a 1-kb long NQO-1 proximal promoter fused with the firefly luciferase gene, and treated them with BG (5-40 mM) for 8 h. Total cell lysate prepared for a luciferase reporter assay showed increased luciferase activity in a dose-dependent manner, suggesting the possibility that BG activates Nrf2 (data not shown).…”
Section: Effects Of Bg On Nrf2 Activation and The Production Of Reactmentioning
confidence: 99%
“…Baicalein, containing an additional OH group in the A ring, showed the most powerful effects. This flavonoid (100  μ M) increased mean, median, and maximum life span by 45, 57, and 24% [39]. …”
Section: Modulation Of Life Span Of C Elegans By Flavonoidsmentioning
confidence: 99%
“…Various types of flavonoids were able to diminish oxidative stress levels induced by heat [3739, 48, 61, 70]. For example, epicatechin treatment decreased intracellular levels of ROS by 24 to 28% [61].…”
Section: Influence Of Flavonoids On the Oxidative Stress Level In mentioning
confidence: 99%